2020
DOI: 10.2217/fmb-2019-0082
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Ketamine and Azole Derivatives onCandidaSpp. Resistance to Fluconazole

Abstract: The emergence of Candida spp. with resistance to antifungal molecules, mainly the azole class, is an increasing complication in hospitals around the globe. Aim: In the present research, we evaluated the synergistic effects of ketamine with two azole derivatives, itraconazole and fluconazole, on strains of Candida spp. to fluconazole. Materials & methods: The drug synergy was evaluated by quantifying the fractional inhibitory concentration index and by fluorescence microscopy and flow cytometry techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
2
10
0
1
Order By: Relevance
“…The activity of etomidate against S. aureus, E. coli, P. aeruginosa, A. baumannii and E. coli ESBL [13] has already been cited in the literature, but its activity against growing biofilms has not yet been reported. The activity of the anaesthetics ketamine and etomidate has recently been demonstrated against clinical fluconazole-resistant Candida isolates in planktonic and biofilm form [12,14]. Another important factor demonstrated in our results was the reduction of C. albicans cell wall mannoproteins caused by treatment with etomidate.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The activity of etomidate against S. aureus, E. coli, P. aeruginosa, A. baumannii and E. coli ESBL [13] has already been cited in the literature, but its activity against growing biofilms has not yet been reported. The activity of the anaesthetics ketamine and etomidate has recently been demonstrated against clinical fluconazole-resistant Candida isolates in planktonic and biofilm form [12,14]. Another important factor demonstrated in our results was the reduction of C. albicans cell wall mannoproteins caused by treatment with etomidate.…”
Section: Discussionsupporting
confidence: 58%
“…Some studies have reported the therapeutic repurposing of anaesthetic drugs. These papers have described the antimicrobial activity of drugs such as propofol, midazolam, ketamine and etomidate against different micro-organisms [12][13][14]. These authors have reported antimicrobial effects against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus hominis, Streptococcus epidermidis, Streptococcus pyogenes, Klebsiella pneumoniae, Acinetobacter baumannii and C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…The terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) method was used to determine DNA fragmentation according to Andrade [25, 26]. The samples were treated with 7 % paraformaldehyde and then with 1 % Triton X-100 for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular sterases hydrolyze CM-H2DCFDA to a non-fluorescent compound (NFC), which is rapidly oxidized to NFDC (2.7=-dichlorofluorescein), a compound that produces high fluorescence. The fluorescence intensity of DCF is proportional to the production of ROS [25,26].…”
Section: Assessment Of the Production Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…Incl. E. dermatitidis [205] ketamine [206] ibuprofen [207] chlorhexidine Incl. C. auris [208] ganetespib [209]…”
Section: D-penicillamineunclassified